2011
DOI: 10.1093/hmg/ddr292
|View full text |Cite
|
Sign up to set email alerts
|

Double-stranded RNA is pathogenic in Drosophila models of expanded repeat neurodegenerative diseases

Abstract: The pathogenic agent responsible for the expanded repeat diseases, a group of neurodegenerative diseases that includes Huntington's disease is not yet fully understood. Expanded polyglutamine (polyQ) is thought to be the toxic agent in certain cases, however, not all expanded repeat disease genes can encode a polyQ sequence. Since a repeat-containing RNA intermediary is common to all of these diseases, hairpin-forming single-stranded RNA has been investigated as a potential common pathogenic agent. More recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(78 citation statements)
references
References 37 publications
3
73
1
Order By: Relevance
“…38 While Pur-α associates with RNAi factors (Fig. S1B), it is dispensable for RNAi and miRNA-mediated silencing (data not shown).…”
Section: Discussionmentioning
confidence: 92%
“…38 While Pur-α associates with RNAi factors (Fig. S1B), it is dispensable for RNAi and miRNA-mediated silencing (data not shown).…”
Section: Discussionmentioning
confidence: 92%
“…Dicer activity on the hairpin-like double-stranded structure in expanded CAG repeats of HTT-e1 results in the biogenesis of small CAG-repeated RNAs (sCAGs) (26) with toxic activity (9). In addition, binding of dicer to expanded CAG repeats has been proposed to contribute to abnormal miR expression profiles that may underlie pathogenic alterations in gene expression (27). To evaluate whether the detrimental effect of sRNAs was reversed by LNA-CTG, we isolated an sRNA-enriched fraction (<200 nt) from the striatum of WT and R6/2 mice injected with LNA-SCB and from R6/2 mice injected with LNA-CTG (pooled extracts from at least 11 mice per condition) and determined cell death after transfection into a differentiated neuronal cell line ( Figure 5A).…”
Section: Resultsmentioning
confidence: 99%
“…Expanded CAG repeats form a hairpin-like secondary structure that causes RNA toxicity through diverse mechanisms involving aberrant interactions with proteins and consequent altered functions (12). These include dicer and nucleolin (NCL), which underlie deleterious sRNA expression profiles (9,27) and decreased Rn45s expression levels mediating nucleolar stress (5, 28), respectively.…”
Section: Knockin Striatal Cells Conditionally Immortalized Wt (Sthdhmentioning
confidence: 99%
“…Expression of the two transcripts led to the generation of Dicer-2 (dcr-2) and ago2-dependent 21-nt TNR-derived siRNAs resulting in high toxicity to the cells. In a separate study, it was shown that expression of these complementary repeat RNAs leads to dcr-2-dependent neurodegeneration [28]. These results suggest that co-expression of CAG and CUG repeat-derived sequences may dramatically enhance toxicity in human repeat expansion diseases in which anti-sense transcription occurs.…”
Section: Discussionmentioning
confidence: 96%